2010
DOI: 10.6004/jnccn.2010.0017
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Screening and Determining the Appropriate Prostate-Specific Antigen Cutoff Values

Abstract: Prostate-specific antigen (PSA) in combination with digital rectal examination forms the basis for current prostate cancer (CaP) screening programs. Although PSA screening was recently shown to reduce CaP-specific mortality in the European randomized trial, its limitations include the risk for unnecessary prostate biopsy and the diagnosis and treatment of some CaP that might never have caused suffering or death. A potential way to minimize these pitfalls is through the use of derivatives of PSA, particularly P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 47 publications
0
10
0
2
Order By: Relevance
“…8 PSA testing has been increasingly used as a screening test for prostate cancer detection, despite its limitations. 9 In our study, approximately every fourth man aged over 40 was screened in primary care during a one-year period. This result is consistent with a questionnaire-based NZ study, which reported screening rates of 18% in 2008 and 22% during the years [2003][2004][2005][2006][2007].…”
Section: Discussionmentioning
confidence: 99%
“…8 PSA testing has been increasingly used as a screening test for prostate cancer detection, despite its limitations. 9 In our study, approximately every fourth man aged over 40 was screened in primary care during a one-year period. This result is consistent with a questionnaire-based NZ study, which reported screening rates of 18% in 2008 and 22% during the years [2003][2004][2005][2006][2007].…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many different views, improvements in new screening tests and treatments since the beginning of 1990s have led to significant improvements in prostate cancer incidence and diagnosis phase and mortality (5,6). However, prostate cancer diagnosed in late stages could become mortal (4).…”
Section: Introductionmentioning
confidence: 99%
“…Early diagnosis of tumor and timely detection of prostate cancer progression following either surgery or radiation therapy are critical for its effective and beneficial clinical outcome. The widespread use of serum-based total prostate-specific antigen (PSA) has led to detection of prostate cancer at a potentially curable stage however, its use as a screening tool remains controversial due to the absence of a true tPSA cutoff-point for identifying prostate cancer risk [3, 4]. First, approximately one-third of prostate cancers detected at a PSA level at or above 4ng/mL have already spread to the prostate capsule or beyond, and approximately 15% of men with a PSA level <4ng/mL have prostate cancer that is detectable by needle biopsy [5-7].…”
Section: Introductionmentioning
confidence: 99%